A new tableaux system for KD - Freitas, Romulo Albano de; Feitosa, Hércules de Araujo (C.Q.D. - Revista Eletrônica Paulista de Matemática, 2020)
The deontic logic is a particular case of modal logic that analyses relations among the concepts of obligation, permission and prohibition. We take the standard deontic logic KD, for which we introduce a new system of tableaux.